Does Maturity Affect Cephalic Perfusion and T/QRS Ratio during Prolonged Umbilical Cord Occlusion in Fetal Sheep? - Guido Wassink; Robert Galinsky; Paul P. Drury; Eleanor R. Gunn; Laura Bennet; Alistair J. Gunn (Obstetrics and Gynecology International)
T/QRS ratio monitoring is used to help identify fetal asphyxia. However, immature animals have greater capacity to maintain blood pressure during severe asphyxia, raising the possibility that they may show an attenuated T/QRS increase during asphyxia. Chronically instrumented fetal sheep at 0.6 of gestation (0.6 GA; n = 12), 0.7 GA (n = 12), and 0.8 GA (n = 8) underwent complete umbilical cord occlusion for 30 min, 25 min, or 15 min, respectively. Cord occlusion was associated with progressive metabolic acidosis and initial hypertension followed by severe hypotension, with a more rapid fall in mean arterial blood pressure (MAP) and carotid blood flow (CaBF) with advancing gestation. T/QRS ratio rose after occlusion more rapidly at 0.8 GA than in immature fetuses, to a similar final peak at all ages, followed by a progressive fall that was slower at 0.8 GA than in the immature fetuses. The increase in T/QRS ratio correlated with initial hypertension at 0.8 GA (P<0.05, R2 = 0.38), and conversely, its fall correlated closely with falling MAP in all gestational groups (P<0.01, R2 = 0.67). In conclusion, elevation of the T/QRS ratio is an index of onset of severe asphyxia in the last third of gestation, but not of fetal compromise.